IMPLEMENTASI PROBLEM BASED-LEARNING (PBL) DAN PENDEKATAN ILMIAH MENGGUNAKAN MEDIA KARTU UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK TENTANG MENGAJAR IKATAN KIMIA - SILABAN, RAMLAN; PANGGABEAN, FREDDY TUA MUSA; HUTAPEA, FELIA MUTIARA; HUTAHAEAN, ESRIDA; ALEXANDER, IRVING JOSAFAT (Jurnal Ilmu Pendidikan Indonesia, 2020)
This study aims to determine whether there is an influence on the implementation of PBL through a scientific approach that provides a media card for high school students' chemistry learning outcomes. To achieve this goal, quasi-experimental research was conducted using two classes, namely the experimental class and the control class. Data obtained using a validated test instrument in the form of pretest and posttest. The results showed that (1). There was an increase in chemistry learning outcomes from the average pretest 27.2 to 63.95 and 72.5 in the two classes of experiment I and experiment II, respectively. (2). Student learning outcomes that are taught with the Problem Based Learning model and the scientific approach provides higher paired cards than using textbook as a media.